Cognitive-behavioral Intervention with a Child with Tourette Syndrome: An Experience Report - Scopel, Ludiane (2015)
This paper aims to present an experience in clinical practice, attended by a trainee in Clinical Psychology of Educational institution. It is about a boy, who is seven years old and with complaints directed to Tourette’s syndrome, showing intense anxiety about the motor and/or vocal tics. The paternal grandmother brought the boy to the service because she observed that these involuntary movements bothered. Interventions based on cognitive behavioral therapy have been performed such as psycho education, with the child and grandmother, as well as the distraction technique, seeking improvement quality of life. From the interventions, it observed gradual improvement in symptoms, where the patient was able to gain greater control over tics, as well as, decrease anxiety front of them.